Interlinkage of Drought, Fire Severity, Vegetation Degradation, and Hydrological Response in Peatland Ecosystems - Mokhamad Yusup Nur Khakim; Azhar Kholiq Affandi; Erni; Mardia Ulfa (Science and Technology Indonesia, 2026)
Peatlands, as fragile ecosystems, are vulnerable to deforestation and altered hydrological regimes. The objectives of this study were to evaluate the effects of deforestation on runoff, drought, and fire severity in nine Peat Hydrological Units (KHG) in South Sumatra, Indonesia, in 2014–2025. The deforestation map was created by analyzing the Landsat-8 image through Spectral Mixture Analysis (SMA) and the Normalized Difference Fraction Index (NDFI). The runoff was modeled using the Soil Conservation Service-Curve Number (SCS-CN) method based on downscaled land cover, CHIRPS, GLDAS, and MODIS data. The drought condition was evaluated using the Vegetation Health Index (VHI), and fire severity was evaluated based on the Relativized Burn Ratio (RBR). The findings indicate that in 2015, the most significant deforestation occurred with the value of NDFI decreasing by > 0.25. In 2015, the highest annual rainfall during the study was 1828 mm, with an anomaly of 1-m topsoil moisture reaching −11.35 mm. Extreme drought (VHI < 0.1) occurred in > 35% of the area of S. Merang – S. Ngirawan and S. Lalan – S. Merang watersheds. Also, the 2015 fires had the largest area of moderate and high (RBR > 0.27) compared to the 2019 and 2023 fires. Deforestation also increased hydrologic response in the watershed as the annual runoff coefficient increased from 13% in 2015 to 15% in 2016 due to a decrease in infiltration from vegetation loss. As a conclusion, this study showed that deforestation increased runoff, drought conditions and peat fires. Our findings are important for evidence-based strategies on fire mitigation and hydrological management in tropical peatlands.